2017
DOI: 10.1016/j.jsv.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Vibration mitigation in partially liquid-filled vessel using passive energy absorbers

Abstract: This paper treats possible solutions for vibration mitigation in reduced-order model of partially-filled liquid tank under impulsive forcing. Such excitation may lead to hydraulic impacts applied on the tank inner walls. Finite stiffness of the tank walls is taken into account. We explore both linear (Tuned Mass Damper) and nonlinear (Nonlinear Energy Sink) passive vibration absorbers; mitigation performances are examined numerically. The liquid sloshing mass is modeled by equivalent massspring-dashpot system,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
(64 reference statements)
0
13
0
1
Order By: Relevance
“…In this case, the mass ratio of the first sloshing mass to the total mass m 1 / m is the maximum value, whereas m 0 / m is the minimum value and the mass ratio of the higher order sloshing mass to the total mass is less than 5%. It is concluded that it is suitable to consider only the first sloshing mass in the equivalent mechanical model of the liquid motion in the cylindrical tank . However, the effect of the second sloshing mass on the equivalent mechanical model of the ATLD should be further investigated.…”
Section: Model Developmentmentioning
confidence: 99%
“…In this case, the mass ratio of the first sloshing mass to the total mass m 1 / m is the maximum value, whereas m 0 / m is the minimum value and the mass ratio of the higher order sloshing mass to the total mass is less than 5%. It is concluded that it is suitable to consider only the first sloshing mass in the equivalent mechanical model of the liquid motion in the cylindrical tank . However, the effect of the second sloshing mass on the equivalent mechanical model of the ATLD should be further investigated.…”
Section: Model Developmentmentioning
confidence: 99%
“…δ t ( ) is the Dirac delta function. Evaluation of realistic values for these parameters is presented in [19]. As explained above, the ratio of masses ε is considered as the small parameter of the problem.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…Expression (19) is valid for n p n N ∀ ∈ : > − ( + 1) without loss of generality, since it requires only p > − 1/2, i.e. expression (19) is valid for every feasible value of p.…”
Section: Derivation Of the Velocity-dependent Restitution Coefficientmentioning
confidence: 99%
“…In previous works, we treated hydraulic impacts regime with the help of reduced-order mechanical models. Both pendulum [10] and mass-spring systems [43], [44] were used to describe the vibro-impact regimes induced under a horizontal ground excitation. Tank elasticity and strongly nonlinear sloshing were considered, and different dynamical regimes were described with asymptotic tools that were validated numerically.…”
Section: Introductionmentioning
confidence: 99%
“…Tank elasticity and strongly nonlinear sloshing were considered, and different dynamical regimes were described with asymptotic tools that were validated numerically. In [44], analysis of realistic partiallyfilled tank was shown and mitigation of vibrations was optimized with the help tuned mass damper (TMD) and nonlinear energy sink (NES).…”
Section: Introductionmentioning
confidence: 99%